(untitled) - Simchi-Levi, David (Boston, 2008)
This book important contribution and major milestone for the supply chain community.
Keywords: Physical distribution of goods,Marketing channels,Business logistics.,Industrial procurement.,Quản lý sản phẩm; Management,Management,Quản trị các kênh quảng cáo